POJĘCIE LEGITYMIZACJI WŁASNOŚCI - Kaczmarczyk, Michał (Wydział Prawa i Administracji UAM, 2002)
The article deals with the sociological theory of property, which belongs to the domain of sociology of law. The author mentions both classic and contemporary sources from the continental and Anglo-American legal tradition. The presented notion is based primarily upon Max Weber’s methodological assumptions and some of its newer interpretations as well as upon the theories of property by Niklas Luhmann, Jeremy Waldron, and Bruce Ackerman. The general theory o f legitimacy has been borrowed from Jurgen Habermas’ works.
NOTION OF PROPERTY LEGITIMACY